Relação entre tamanho corporal e estrutura de comunidade em anfíbios anuros do município de Botucatu/SP - Teixeira, Maria Gorete [UNESP] (2013)
The species coexistence in a given community is possible in function of species resources partitioning, among many other factors. The selective pressures which determine the pattern of occupation by species may be directly related to their morphology. In the present study, we investigated the relationship of body size and morphology of 42 species of anurans with their spatial and temporal distribution. The study hypothesis is that body size influences their habitat and behavior. Morphological characters were analyzed regarding to temporal distribution and to ecological indexes (spatial distribution) using conventional and phylogenetic approaches. The results indicate that smaller species are more abundant than large ones, and that there was no significant variation in of total mass (biomass) when analyzed per size classes. There were constraints in species distribution regarding to size. The principal components analyses revealed morphological relations of length and width that refer to typical anurans body shapes of certain habits and habitats. The analysis of Morisita-Horn showed high temporal overlap on the environment occupation between size classes. Descriptive analyses indicated differences in habitat occupation and habit among frogs of different sizes. The Kruskal-Wallis test indicated no relationship between snout-vent length and the habit of anurans. However, the results indicated that species with different body masses have different habits and abundances. Phylogenetic signal was detected in three of four principal components tested, as well as in four of seven ecological indexes tested. The results indicate that environmental indexes are related to anurans morphology, suggesting that environment type and how it is occupied are good predictors to infer body shape. The results indicated that size, duration and regime of water bodies do not influence size and morphology of adult anurans. These ecological factors may be more ...